Transparency and open data in the classroom: A pedagogical exercise to construct civic awareness about access to public digital data in Brazil - Berrio-Zapata, Cristian; Santana, Ricardo Cesar Goncalves [UNESP] (Inderscience Publishers, 2015)
This paper presents the pedagogical experience of the open data administration course whose acronym in Portuguese is 'ATADA', at UNESP, Brazil. After some theoretical explanations about data transparency limitations in the day-to-day of the citizen, we present this experience based in Paulo Freire's Pedagogy of Autonomy. Brazilians seem not to have yet a clear perspective on this topic, or the necessary awareness to test the real existence of transparency and openness in their life. ATADA course was designed to introduce students in the field using participatory action research (PAR), creating research communities. In doing so, ATADA research communities reviewed 19 cases of Public Data into Brazilian e-government sites. The results of the two first versions of ATADA, developed in 2011 and 2012, are presented as well as two concepts produced to describe our findings regarding open access and data transparency: the 'minimum legal bureaucratic template' and 'data opacity'.
Keywords: E-government; E-literacy; I-literacy; ICT; Information and communication technologies; Open data; PAR; Participatory action research; Paulo Freire; Transparency